White collar productivity: The search for the holy grail - Conrath, David W. (Journal of business ethics, 1984)
The search for increased productivity has led to a great many claims about how it might be accomplished. Nowhere have the claims been more brazen and yet less well supported empirically than those made on behalf of the technologies designed to support office work. The paper examines some of the arguments and claims made, suggesting that most of them are off target. While the new technologies may be of substantial value, the emphasis should beon increased effectiveness, not on greater efficiency. Only then are the visions of the future likely to be fulfilled.